Anion recognition by silanetriol in acetonitrile. Issue 45 (2nd November 2022) - Kondo, Shin-ichi; Okada, Natsumi; Abe, Shiori; Tanaka, Ryoji; Yamamura, Masaki; Unno, Masafumi
Abstract : Anion recognition ability and organocatalytic activity of a silanetriol are firstly presented by comparing with those of a series of silanol derivatives. Abstract : The anion recognition ability of 2, 4, 6-triisopropylphenylsilanetriol 5 has been evaluated by 1 H NMR titrations in MeCN- d 3 . The anion recognition ability of silanetriol 5 was greater than those of the structurally related silanediols and silanemono-ol, although less effective than those of 1, 3-disiloxane-1, 3-diol and 1, 3-disiloxane-1, 1, 3, 3-tetraol. From the comparison of the association constants and DFT calculations, all three silanol groups of 5 cooperatively hydrogen bonded to anionic species. The catalytic ability of silanetriol 5 for the addition of indole to β-nitrostyrene in CH2 Cl2 has also been evaluated. Silanetriol 5 acts as a more effective organocatalyst than the corresponding silanediol in this reaction.